PENGARUH KEPEMIMPINAN KEPALA DESA, PARTISIPASI MASYARAKAT DAN KOMUNIKASI TERHADAP KEBERHASILAN LOMBA DESA: (Studi di Desa Paringan, Kecamatan Jenangan Kabupaten Ponorogo Provinsi Jawa Timur) - Evita Arisanti; Herning Suryo Sardjono; Suwardi Suwardi (Master of Public Administration, Universitas Slamet Riyadi, 2023)
The purpose of this study was to describe the effect of village head leadership, community participation and communication on the success of village competitions. This type of research is survey and classified in explanatory research. This research was conducted in Paringan Village, Jenangan, Ponorogo. The population in this study was a village competition team, totaling 48 people. The sampling technique was a census where the entire population was the sample. Data collection techniques used questionnaires and literature study. The data analysis technique used multiple linear regression. The results showed that the leadership of the village had a positive and significant effect on the success of the village competition in Paringan Village, Jenangan District, Ponorogo Regency. Community participation has a positive and significant effect on the success of the village competition in Paringan Village, Jenangan District, Ponorogo Regency. Communication has a positive and significant effect on the success of the village competition in Paringan Village, Jenangan District, Ponorogo Regency. The leadership of the village head, community participation and communication simultaneously influence the success of the village competition in Paringan Village, Jenangan District, Ponorogo Regency. Keywords: leadership, participation, communication, village competition success